Bio-assay guided fractionation of hypotensive compounds from syzygium polyanthum wight (WALP.)Var. Polyanthum leaves - Ismail, Azlini; Omar, Muhammad Nor; Wan Ahmad, Wan Amir Nizam; Abd Rahim, Erlena Nor Asmira (2018)
Syzygium polyanthum (Wight) Walp. has been known as antihypertensive medicinal plant and the leaves are regularly consumed by the locals as fresh salad. Previous studies have reported on its antihypertensive effect but the responsible bioactive compounds were still unknown. The present study aimed to screen the potential antihypertensive compound(s) from the most active crude extract through bio-assay guided fractionation and to examine correlation of the effect with total phenolic content (TPC) and ferric reducing antioxidant power (FRAP) activity. S. polyanthum leaves were partitioned by sequential solvent extractions with hexane, ethyl acetate, methanol and water to obtain crude hexane extract (HSP), ethyl acetate extract (ESP), methanol extract (MSP) and aqueous extract (ASP). Then, these four extracts were intravenously administered in pentobarbital-anaesthetized Spontaneously Hypertensive Rats (SHR) (n=5) for measurement of mean arterial, systolic, and diastolic blood pressures, as well as the heart rate. The most active crude extract was then fractionated in a column chromatography using binary solvent system of ethyl acetate and methanol. Thin layer chromatography (TLC) profiling was done to pool out fractions derived from the active crude extract. These fractions were then intravenously administered in pentobarbital-anaesthetized SHR (n=5) for measurement of blood pressure and heart rate parameters and these were then compared with the effect of 5 mg/kg of captopril, a standard antihypertensive drug. One-way and two-way ANOVA were used for data analyses. The phytochemical constituents in the fractions were analyzed using Liquid Chromatography Mass Spectrometry (LC-MS). In addition, analysis of TPC and FRAP assay were conducted on the fractions, any potential correlation with antihypertensive activity was tested using Pearson’s Correlation test. This study showed that ESP, MSP and ASP were found to exert significant antihypertensive effect, with ASP as the most prominent crude extract. Fractionation of ASP resulted into 9 fractions, which were then combined into 3 final fractions (F1ASP, F2ASP and F3ASP) according their TLC profiles. F2ASP was found to be the most active fraction, and its antihypertensive effect was actually more potent compared to other fractions as well as the crude ASP extract. Magnitude of F2ASP effect was actually comparable with captopril (5mg/kg, i.v). Chemical profiling using LC-MS revealed the presence of several bioactive compounds with potential in causing antihypertensive effect such as 1-galloyl-glucose, polydatin, sesamol, brazilin, eugenol, ellagic acid, kukoamine A and cyclocurcumin. TPC and antioxidant activity of ASP crude extract and the three derived fractions were positively correlated and in the following order: ASP > F1ASP > F3ASP = F2ASP. It was also found that even ASP crude extract and the three derived fractions have both antihypertensive and antioxidant activity, however, these activities were not significantly correlated in this study. In conclusion, this study showed antihypertensive effect of S. polyanthum leaves but the magnitude of the effect was not correlated with either TPC content or antioxidant activity.